Effect of a brief dietary counselling intervention on emergency department cardiac chest pain presentations. Issue 2 (1st July 2022) - Murphy, Ronan; Al Rasheed, Ahmed; Keaver, Laura
Abstract : Introduction: 15% of all presentations to our emergency department last year were chest pain related. This presented an opportunity to evaluate the impact of a brief physician counselling intervention on patient-reported changes in cardio-protective foodstuff intake. Methods: This is a prospective non-randomised before and after comparison study without controls, conducted between an emergency department presentation and a scheduled follow-up visit at a cardiac diagnostics department. Participants were recruited between February and March 2021. The selected dietary components for inclusion after review of the literature were green leafy vegetables, other coloured vegetables, wholegrains, legumes and fruits. A food frequency questionnaire was completed by patients before and after a physician counselling intervention aided by a dietary infographic. Additionally, using the transtheoretical model for health behaviour change, we assessed each patient's evolution during the study. Results: 38 patients were recruited. For patients with total baseline consumptions of five or fewer per day, there was an increase in cardioprotective foodstuff intakes (z=−2.784 p<0.005 effect size 0.39). Corresponding to this, there was a participant shift observed towards the action and maintenance phases of behaviour change from the contemplation and preparation phases. Discussion: We demonstrated a statistically significant change with moderate effect size using a simple infographic, coupled with brief physician counselling, to promote increased intake of cardioprotective foodstuffs by patients with poor baseline intakes (<5 cardio-protective foods per day) and known modifiable risk factors for ischaemic heart disease. Conclusion: Diet is one arm in the prevention of cardiovascular disease that is often neglected by physicians. This study found that a brief dietary counselling intervention applied in an emergency department setting, administered by non-nutritionists can have a role in changing patient dietary behaviour.